PEMANFAATAN GIS DAN AHP DALAM PENERIMAAN DANA BOS JENJANG SMA - Juniar Hutagalung; Azlan Azlan (STMIK Royal, 2020)
Abstract: This study illustrates the use of the Analytical Hierarchy Process (AHP) in a decision support system (SPK) and combined with the Geographic Information System (GIS) to select funds for School Operational Assistance (BOS) at the secondary school level as a recommendation. for decision-makers, so that the selection of BOS fund receipts can run properly, quickly and as expected. The problem of delays in the distribution of BOS funds and the price of goods that can change every year, thereby affecting the unstable amount of funds spent on operational costs. The purpose of this study is to utilize a decision support system in determining the priority of receiving BOS funds at the secondary school level using the AHP method combined with GIS so that the implementation of the information system can be optimized. With this system, it is very useful to monitor the distribution of BOS funds so that they run smoothly by the expectations and goals of government programs. Determination of latitude and longitude using google maps to obtain maps and locations of aid recipients, connected with MySQL as a database and PHP programming and modeled with UML. The results of this study can be used to determine the receipt of BOS funds and their mapping by providing various criteria and alternatives for decision-makers. Keywords: AHP, BOS, GIS, Google Map, SPK Abstrak: Penelitian ini memaparkan tentang pemanfaatan Analitical Hierarchy Process (AHP) dalam sistem pendukung keputusan (SPK) dan dikombinasikan dengan Geographic Information System (GIS) untuk menyeleksi penerimaan dana Bantuan Operasional Sekolah (BOS) jenjang SMA sebagai rekomendasi bagi pihak pengambil keputusan, agar seleksi penerimaan dana BOS tersebut dapat berjalan secara tepat, cepat dan sesuai dengan yang diharapkan. Masalah keterlambatan pada saat penyaluran dana BOS dan harga barang-barang yang setiap tahunnya bisa berubah sehingga berpengaruh terhadap tidak stabilnya jumlah pengeluaran dana untuk biaya operasional. Tujuan yang ingin dicapai dari penelitian ini adalah pemanfaatan sistem pendukung keputusan dalam menentukan prioritas penerimaan dana BOS jenjang SMA dengan menggunakan metode AHP dikombinasikan dengan GIS, sehingga implementasi sistem informasi dapat optimal. Dengan adanya sistem ini bermanfaat untuk memantau penyaluran dana BOS agar berjalan dengan lancar sesuai dengan harapan dan tujuan dari program pemerintah. Penentuan latitude dan longitude menggunakan google maps untuk mendapatkan peta dan lokasi penerima bantuan, dikoneksikan dengan mysql sebagai database dan pemrograman PHP serta dimodelkan dengan UML. Hasil penelitian ini dapat digunakan untuk menentukan penerimaan dana BOS dan pemetaannya dengan memberikan berbagai kriteria dan alternatif kepada pihak pengambil keputusan. Kata kunci: AHP, BOS, GIS, Google Map, SPK